Kesesuaian Fatwa DSN MUI No.7/DSN-MUI/IV/2000 Dalam Produk Pembiayaan Kepada Koperasi Untuk Anggota (PKPA) di Bank Jatim Syariah Cabang Darmo Kota Surabaya - Alfina Taswirul Fanni; Ari Prasetyo (Universitas Airlangga, 2017)
This research purpose is to knowing the conformation of Mudharabah Agreement in the financing mechanism in Syariah Bank Surabaya based on the DSN MUI Decision NO: 07/DSN-MUI/IV/2000Bank Jatim Branch Syariah Darmo Surabaya. This research uses qualitative method with descriptive case study and purposive sampling technique. The data which is used in this research is obtained by semi-structured interview and the data analysis is using descriptive analysis modelThis research indicates that “Bank Jatim Syariah Branch Darmo Surabaya” in performing Mudharabah mechanism are acting in approriate with DSN MUI Decision NO: 07/DSN-MUI/IV/2000 properly. It is indicated with the implementation SOP product with Mudharabah Aggrement which conducted by the regulation of Fatwa DSN MUI NO: 07/DSN-MUI/IV/2000. It starts with the general provisions of Mudharabah Aggrement, pillars and conditions of Mudharabah Aggrement, and law financing of Mudharabah Aggrement. The implementation of this concept has been contributing much benefit to every parties involved.